2017
DOI: 10.1080/08923973.2017.1392564
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of icaritin on hematopoietic function in cyclophosphamide-induced myelosuppression mice

Abstract: These results demonstrated that ICT improves myelosuppression by improving bone marrow hematopoietic microenvironment, promoting the proliferation and differentiation of HSCs, inhibiting the apoptosis of HSCs and stimulating the expression of G-CSF and TPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…The results indicated that CTX decreased the spleen index and numbers of lymphocytes, increased numbers of cells with nuclear shrinkage and apoptosis, and caused aberrations in spleen morphology and an imbalance of leukocytes; these findings revealed that immunosuppression in geese was induced successfully. The reason may be that CTX inhibits the production of bone marrow hematopoietic stem cells, reduces the number of new differentiated leukocytes but also accelerates the atrophy and apoptosis of leukocytes [ 20 ]. This study found that PAMK significantly increased the CTX-inhibited spleen index, mainly by significantly increasing the spleen weight of geese.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that CTX decreased the spleen index and numbers of lymphocytes, increased numbers of cells with nuclear shrinkage and apoptosis, and caused aberrations in spleen morphology and an imbalance of leukocytes; these findings revealed that immunosuppression in geese was induced successfully. The reason may be that CTX inhibits the production of bone marrow hematopoietic stem cells, reduces the number of new differentiated leukocytes but also accelerates the atrophy and apoptosis of leukocytes [ 20 ]. This study found that PAMK significantly increased the CTX-inhibited spleen index, mainly by significantly increasing the spleen weight of geese.…”
Section: Discussionmentioning
confidence: 99%
“…CY is also a cytotoxic drug, but it has no activity in vitro, and it can damage the structure of DNA, cut off its copy that can lead to cell death in vivo [ 16 , 17 ]. Research showed that the long-term use of CY had harmful side effects, such as immunosuppression, myelosuppression and leucopenia [ 18 ]. Most importantly, immunosuppression was one of the major side effects of using high doses of CY.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, chemotherapeutics drugs often generate many harmful side effects such as cytotoxic effects and host immunosuppression, no matter how great of their therapeutic effects are [ 4 ]. Cyclophosphamide (Cy), an alkylating agent, has been widely used as chemotherapeutic drug which results in a lot of adverse effects including immunosuppression, bone marrow suppression, leucopenia and oxidative stress [ 5 , 6 , 7 , 8 ]. It has been reported that Cy can generate oxidative stresses, mediate disruption of the redox balance, and lead to biochemical and physiological disturbances [ 9 ].…”
Section: Introductionmentioning
confidence: 99%